ALLELOPATHIC EFFECT OF WATER EXTRACTS OF SORGHUM HALEPENSE (L.) PERS., CONVOLVULUS ARVENSIS L. AND CIRSIUM ARVENSE SCOP. ON THE EARLY SEEDLING GROWTH OF SOME LEGUMES CROPS (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
In order to study the allelopathic effect of aboveground dry biomass of Sorghum  halepense,  Convolvulus arvensis and Cirsium arvense on seed germination and early seedling growth of Pisum sativum (L.), varieties Mir (winter form) and Kerpo (spring form); Vicia sativa (L.), variety Tempo, and Medicago sativa (L.), variety Dara, a laboratory experiment was conducted at the Institute of Forage Crops - Pleven. Four  concentrations: 1.25, 2.5, 5.0 and 10.0% were applied to each weed biotype used to study allelopathic effects. The results showed that weed extracts significantly decreased germination percentage, shoot and root length (cm), shoot and root weight (g), and seed vigor index (SVI1 and SVI2) of the tested species. In general, the variable effects are related to the weed species and extract concentrations.
Keywords: Allelopathy; Plant extracts; Leguminosae; Weeds